Consortium Negotiations with Publishers - Past and Future - Carbone, Pierre (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
Since the mid nineties, with the development of online access to information (journals, databases, e-books), libraries strengthened their cooperation. They set up consortia at different levels around the world, generally with the support of the public authorities, for negotiating collectively with the publishers and information providers general agreements for access to these resources. This cooperation has been reinforced at the international level with the exchange of experiences and the debates in the ICOLC seminars and statements. So did the French consortium Couperin, which is now gathering more than 200 academic and research institutions. The level of access and downloading from these resources is growing with geometrical progression, and reaches a scale with no comparison to ILL or access to printed documents, but the costs did not reduce and the libraries budgets did not increase. At first, agreements with the major journal publishers were based on cross-access, and evolved rapidly to the access at a large bundle of titles in the so-called Big deal. After experiencing the advantages of the Big deal, the libraries are now more sensitive to the limits and lack of flexibility and to cost-effectiveness. These Big deals were based on a model where online access fee is built on the cost of print subscriptions, and the problem for the consortia and for the publishers is now to evolve from this print plus online model to an e-only model, no more based on the historical amount of the print subscriptions, to a new deal. In many European countries, VAT legislation is an obstacle to e-only, and this problem must be discussed at the European level. This change to e-only takes place at a moment where changes in the scientific publishing world are important (mergers of publishing houses, growth of research and of scientific publishing in the developing countries, open access and open archives movement). The transition to e-only leads also the library consortia to deal with issues as preservation of print and electronic materials and perennial access to information.